Amborella trichopoda - Bernadette Grosse-Veldmann; Nadja Korotkova; Bernhard Reinken; Wolfram Lobin; Wilhelm Barthlott (Sibbaldia, 2011)
Amborella trichopoda Baill., the most ancestral angiosperm, has been successfully cultivated in the Botanic Gardens of the University of Bonn in Germany (BG Bonn) for more than a decade. The distribution of this plant – limited to the South Pacific island of New Caledonia – and its cultivation has so far only been achieved in a few botanic gardens. This paper provides details about the cultivation and propagation of Amborella, and information on its cultivation in botanic gardens around the world. The authors propose that the collections of this plant in botanic gardens could be used to establish ex situ conservation collections.